Little Lord Fountleroy - Cromwell, John ([Dunellen, N.J.] : Digiview Productions, 2004)
An impoverished New York youngster becomes heir to his titled grandfather's British estate.
Based on the novel by Frances Hodgson Burnett.
Originally released as a motion picture in 1936.
Cinematography, Charles Rosher ; editor, Hal C. Kern ; music, Max Steiner
Keywords: Burnett, Frances Hodgson -- 1849-1924 -- Film adaptations; Grandfathers -- Drama; Poor children -- Drama